Development of a method for the analysis of the lists of medicines and its application for the analysis of the lists of medicines in Russia, England, and Italy - V. A. Lemeshko; K. I. Matrenin; V. V. Omelyanovskiy; Yu. V. Vasilyeva; G. R. Khachatryan; L. A. Kolganov (IRBIS LLC, 2021)
Objective: the development and approbation of the method for comparative analysis of the lists of medicines in different countries and systems of healthcare.Material and methods. Based on the open-access data on the lists of medicines published on official websites of the authorized regulators, the authors selected the national lists of medicines of Russia, England, and Italy for the development and approbation of the method. It was proposed to use three parameters: the absolute number of medicines by international nonproprietary name (INN); the structure of the lists based on anatomical therapeutic chemical (ATC) classification; and the coverage of the indications based on the International Classification of Diseases, 10th edition (ICD-10). The results of the analysis provided grounds for the review of the approaches to the formation of the lists of medicines required for medical help in Russia, England, and Italy and reimbursed from the state budget.Results. The number of medicines by INN in the national lists of England and Italy exceeds the total number of drugs included in the list of vital essential and desirable (VED) in Russia. All the analyzed lists were characterized by an uneven distribution of medicines within the lists by the ATC groups. The lists of medicines in England and Italy significantly exceed the list of VED by the number of the included medicines by all ATC groups excluding groups J and H in comparison with Italy, and groups J and V in comparison with England. At the same time, the list of VED significantly exceeds the list in England by the number of covered indications from the ATC L group. During the approbation, the method showed to be effective and can be used for further comparative studies of the national lists of medicines.Conclusion. Non-uniform lists of medicines by ATC-codes show that each country has priority areas in their healthcare systems. The list of VED can be shorter by the absolute number of the included medicines in England and Italy but it can exceed them by the coverage of indications due to peculiarities of the procedure of the list formation (reimbursement of medicines by all the registered indications). The results of the study with the proposed method can serve for the optimization of the VED list and the analysis of therapeutic areas that are undercovered.